Supramolecular feature of a new dihydrogen phosphate hybrid incorporating 6-amino-1H-indazole: Synthesis, crystal structure, Hirshfeld surfaces analysis, vibrational spectroscopy and optical properties - Emna Bouaziz; Oumaima Mastouri; Mohamed Boujelben; Serhan Alshammari; Ahmed Osman Ibrahim; Mohamed Boujelbene (Results in Chemistry, 2024)
A supramolecular structure is formed during the synthesis of a dihydrogen phosphate hybrid salt with the organic aromatic amine molecule 6-amino-1H-indazole. This work looks into the interactions between 6-amino-1H-indazole molecules and dihydrogen phosphate ions, which sheds light on the formation mechanisms and stability of the resulting crystal lattice. A slow evaporation process resulted in single crystal formation of [C7H9N3][H2PO4]2. The compound crystallizes in the centrosymmetric space group of the monoclinic system, with dimensions a = 7.074(13)Å, b = 14.134(3)Å, c = 12.716(3)Å, β = 91.231(15)°, and Z=4. Hydrogen bonds are essential for connecting the dihydrogen phosphate anions [H2PO4]- and the organic cations [C7H9N3]2+ in the mineral structure. According to Hirshfeld’s analysis oxygen-hydrogen interactions are the most important in the crystal of all potential chemical linkages. The IR and Raman spectra of the chemical collected at room temperature were analyzed in relation to literature data and theoretical groupings. Photoluminescence and UV measurements are linked to a number of electrical activities in the title chemical.